Revealing patterns in improving the performance of portable smoke and heat removal devices when using fine sprayed water - Tsapko, Yuriy; Nizhnyk, Vadym; Prisyazhnuk, Vitally; Benediuk, Vadym; Klymas, Ruslan; Lushch, Vasyl; Parkhomenko, Volodymyr-Petro; Velykyi, Yarema (Eastern-European Journal of Enterprise Technologies, 2024)
An issue related to the application of portable smoke and heat removal devices for buildings and structures is to provide for their effectiveness when removing smoke and reducing temperature. That us why the object of this study was a change in the performance of a portable smoke and heat removal device when using finely sprayed water. Improved efficiency of the use of portable smoke and heat removal devices was based on experimental studies. It was proved that the reduction of smoke concentration and temperature in the room to the initial conditions was achieved for independent smoke dispersion in 5340 s, and cooling occurred in 3120 s. With the use of a smoke and heat removal agent during air supply, the smoke dissipated in 720 s, and cooling took 1560 s. And with the simultaneous supply of air and a sprayed jet of water, smoke dispersal occurred in 360 s, and cooling in 1020 s, respectively. To determine the efficiency of the smoke and heat release device, a calculation-experimental method has been devised that makes it possible to estimate the coefficient of the smoke and heat release agent when supplying air and water. According to experimental data, it was calculated that the coefficient of effectiveness of the smoke and heat removal devices when supplying air and water compared to the means when supplying only air increases by 2.1 times. The practical significance is that the results were taken into account when devising methodical recommendations for extinguishing fires. Thus, there are reasons to assert the possibility of targeted regulation of the processes of smoke reduction and temperature reduction through the use of a smoke and heat release device that simultaneously supplies air and finely sprayed water